Age and weight estimate on the first breeding in the Brazilian Pantanal heifers - Sereno, José Robson Bezerra; Pellegrin, Aiesca Oliveira; Lara, Maria Aparecida Cassiano; Abreu, Urbano Gomes Pinto de; Sereno, Fabiana Tavares Pires de Souza; Chalita, Liciana Vaz de Arruda Silveira (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this work was to estimate the age and live weight at the first breeding in the Nelore (N), Pantaneira (P), and crossbreeding Pantaneira x Nelore (PxN) heifers. A total of 98 females was used for treatments, 51, 24 and 23 from N, P and PxN heifers, respectively. The statistical analysis did not show any significant difference (P = 0.3595) to live weight in the first breeding among breeds. The variance analysis did not show any significant difference (P = 0.307) of age among breeds, showing 3.5, 3.4 and 3.2 years to P, N and ½PxN heifers, respectively.